Profiling of Canonical and Non-Traditional Cytokine Levels in Interferon-β-Treated Relapsing–Remitting-Multiple Sclerosis Patients - D’Angelo, Chiara; Reale, Marcella; Costantini, Erica; Di Nicola, Marta; Porfilio, Italo; de Andrés, Clara; Fernández-Paredes, Lidia; Sánchez-Ramón, Silvia; Pasquali, Livia (Frontiers in Immunology, 2018)
Background Multiple sclerosis (MS) is a chronic, progressive autoimmune disease of the central nervous system in which inflammation plays a key role in the induction, development, and progression. Most of the MS patients present with relapsing–remitting (RR) form, characterized by flare-ups followed by periods of recovery. Many inflammatory and anti-inflammatory cytokines have been proposed as backers in MS pathogenesis, and the balance between these differing cytokines can regulate MS severity. Interferon (IFN)-β, a current disease-modifying therapy for MS, has demonstrated beneficial effects in reducing disease severity in MS patients. However, its immunoregulatory and anti-inflammatory actions in MS are not wholly understood. The aim of the study was to define, in clinically stable patients with RR-MS, the serum concentration of several cytokines, canonical or not, and their modulation by IFN-β therapy. Methods Relapsing–remitting-MS patients were enrolled and diagnosed according to revised Mc Donald Diagnostic Criteria. A set of cytokines [including non-canonical neurotransmitter acetylcholine (ACh) and adipokines] and B-cell differentiation molecules, as potential biomarkers, were evaluated in 30 non-treated RR-MS patients compared to 30 IFN-β-treated MS patients and 30 age, gender, and body mass index-matched healthy controls (HC). Results Naïve MS patients showed significantly higher levels of interleukin (IL)-1β, IL-12/IL-23p40, IL-18, high-mobility group box protein-1, and IL-18 binding protein (IL-18BP) than MS-treated patients (p < 0.001 for all) and HC (p < 0.01). IFN-β therapy has significantly downmodulated IL-1β, IL-12/IL-23p40, IL-18 to normal levels (p < 0.001), whereas it has decreased IL-18BP (p < 0.001). ACh was significantly higher in the IFN-β-treated than HC and non-treated MS patients (p < 0.001). No significant differences were observed either in adipokines concentration or in B-cell-associated molecules among the three study groups. Conclusion Although more experimental evidence are required, we speculate that the efficacy of treatment of MS with IFN-β is mediated, at least in part, by its ability to work on several levels to slow down the disease progression. Proposed actions include the modulation of IL-1–inflammasome axis and modulation of ACh, B-cell activating factor/a proliferation-inducing ligand system, and several adipokines.